„Zrobić” tekst. O kompetencji tekstotwórczej gimnazjalistów - Anna Wileczek (Postscriptum Polonistyczne)
Is a text for the modern young man a communication anachronism? In this era of communication practices based on fast, informative or ludic transmission, competencies related to the necessity to create coherent, effective and correct texts are disappearing. This article presents a diagnosis of high school students’ communication skills in this area with reference to the educational documents (Core Curriculum) and selected writings – from student work and external examinations. After analyzing the results there are a number of conclusions that can be drawn about the school educational practices. Firstly, centrally proposed programs do indeed raise the awareness of the need for certain text exponents in different genres, but analytical operations associated with the analysis of fragments of texts do not contribute to student’s thinking about the text as a coherent whole. Secondly, the emphasis on recreating a particular structure of the text in the genre (which is most likely to appear during an exam), contributes to a certain mechanical behavior in that regard.